The Reliability and Validity of the Levels of Emotional Awareness Scale for Children (LEAS-C) in Chinese Children - Zhang, Pengcheng; Wang, Zhe; Shen, Yongjiang; Wang, Haibin (Journal of Psychology and Psychotherapy Research, 2016)
Objective: To revise and explore the application of the Levels of Emotional Awareness Scale for Children (LEAS-C) in Chinese Children. Methods: 417 Primary school students from grade four and five were surveyed by the Chinese version of the Levels of Emotional Awareness Scale for Children (LEAS-C) and the Questionnaire on Youth’s Emotional Intelligence (QYEI). Results: (1) The LEAS-C contained self and other two dimensions, and the intra-class correlation coefficient of the overall scale and two subscales were more 0.88 and 0.89 respectively, the Cronbach’s alpha coefficient of full and two subscales were more 0.90, 0.89, and 0.88 respectively, the split-half reliability of the overall scale and two subscales were 0.86, 0.82, and 0.83 respectively; (2) the correlation between two subscales of LEAS-C was 0.87, and the correlation between the total scores and the two subscales were 0.93 and 0.95 respectively; (3) significant positive correlations were found between LEAS-C and QYEI; and (4) the scores of females were higher than those of male on self-, other- and total-LEAS-C scores. Conclusion: The Levels of Emotional Awareness Scale for Children (LEAS-C) has good reliability and validity and can be used in Chinese Children.